NIT: A dataset for network intent translationHugging Face - Ala' A. AlSamarneh; Omar Y. Al-Jarrah; Ahmad T. Al-Hammouri (Data in Brief, 2025)
This paper introduces the NIT (Network Intent Translations) dataset. The NIT dataset is designed for network intent translations, specifically for intent-to-vendor translations. The dataset contains network configuration scenarios described in natural language (intents) and their corresponding low-level configurations for Juniper EX3300 switches with JUNOS Base OS boot [12.3R12-S12]. The dataset was generated following quality measures by validating the correctness of each completion on a Juniper Ex3300 switch and verifying the syntax using configuration manuals. The dataset underwent several revisions to ensure consistent formatting, correct parameter extraction, and accurate outcomes. The dataset is designed to provide translations of high-level network intent to command-line configuration only. It does not target verifying the correctness of the parameters' values in the prompts or any other type of conflict detection or resolution. Despite this, all parameter values included in the dataset are valid values for the corresponding task. The dataset contains 1000 entries; each entry is presented using a JSON object of three elements: question, context, and answer. The question represents the high-level network intent, while the answer represents the corresponding low-level configurations. The context includes the generic form of the low-level configurations. The dataset is suitable for network intent translation research.